Clinical updates on tyrosine kinase inhibitors in HER2-positive breast cancer - Singh, Desh Deepak; Lee, Hae-Jeung; Yadav, Dharmendra Kumar (Frontiers in Pharmacology, 2022)
Breast cancer (BC) is caused by epigenetic modifications and genetic heterogeneity and exhibits various histological feature. HER2+ (Human epidermal growth factor receptor 2) is a more aggressive type of BC, diagnosis and prognosis are difficult for HER2+ BC. Anti-HER2+ inhibitors have been effectively used for patient treatment. High mortality rate is reported in HER2+ BC, due to availability of limited therapeutic options. Despite advances in systemic medications to treat metastatic breast cancer (MBC), HER2-positive MBC is still challenging for patients and treating clinicians. The clinical characteristics of the disease have changed after treatment with HER2-targeted therapy. Various types of Tyrosine kinase inhibitors (TKIs) have been developed to treat patients with HER2+BC including afatinib, lapatinib, neratinib, tucatinib, and pyrotinib, have been developed as HER2-targeted therapies. The antibody-drug conjugates adotrastuzumab, emtansine, famtrastuzumab, and deruxtecan, as well as the anti-HER2 monoclonal antibody pertuzumab are used in both early-stage and metastatic situations, either alone or in conjunction with chemotherapy and other HER2-targeting therapies. The emergence of drug resistance in anti-HER2 therapies has been observed. To overcome drug resistance and limited efficacy in current treatment options, nano formulations can be used in patients with HER2+BC treatment. Anti-HER2 ligands can be used in various nano formulations to target HER2 receptors. Here we will discuss, targeted TKIs in patients with HER2+BC, clinical studies of HER2+ targeted TKIs, mechanisms of resistance to HER2-directed therapies with new implications of TKIs in HER2+ MBC (metastatic breast cancer) and anti-HER2 ligand in various nano formulations to target HER2 receptors.